If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 9x + -6 Reorder the terms: 0 = -6 + 9x Solving 0 = -6 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 0 + -9x = -6 + 9x + -9x Remove the zero: -9x = -6 + 9x + -9x Combine like terms: 9x + -9x = 0 -9x = -6 + 0 -9x = -6 Divide each side by '-9'. x = 0.6666666667 Simplifying x = 0.6666666667
| -16=8x | | 23=18+5x | | e=9-2e | | 4x=6x-11 | | 40=41+x | | 18y-6=-18 | | 18y-6=-10 | | 6p-5=7 | | 30=15x | | t=15x | | 6y^3-7y^2-7y+6=0 | | 20z-1+36=5z+5 | | 30-x=10+0.5x | | 11=21a | | 6m=x | | 4(-2z-5)-7=10 | | 35-6= | | 100*20= | | 3r+10=2(-3r+8) | | (5x-4)3-5(4-3x)=7x+7(3x-4) | | h-13=78 | | 5p-3tq=2 | | 7x-36=3x | | 10x+13=68-x | | 9y^2-12y+1=0 | | 3x+8=2x+20 | | 7(3x+4)=9x-12-x | | 2x+3+4x+2=11 | | 13x-(25+11x)=165-2(4x+10) | | 16x^2-13x=0 | | 5x+37=179 | | 12-3(2x+9)=15 |